The Deuteronomist's history: the role of the Deuteronomist in historical-critical research into Genesis-Numbers - Ausloos, Hans (Oudtestamentische studie͏̈n, 2015)
Preliminary Material -- 1 Deuteronom(ist)ic Elements in Genesis–Numbers: Origin and Evolution of a Problem -- 2 Deuteronom(ist)ic Elements in Genesis–Numbers since the Beginning of the 20th Century -- 3 Proto-Deuteronomic Elements in Genesis–Numbers: A Unique Aspect of Research into the So-Called Deuteronom(ist)ic Elements since 1963 -- 4 The Deuteronom(ist)ic Problem since the Second Half of the 20th Century -- 5 The Deuteronom(ist)ic Problem—A Review and a Preview -- Bibliography -- Index of Authors -- Index of Biblical References.